Corporate Governance in Nepalese Insurance Company - Acharya, Tej Prasad (Damak Campus Journal, 2023)
Corporate governance is one of the best systems by which corporate organizations are guided and managed, Nepalese corporations are realizing the need to initiate good corporate governance practices to create enterprise value. The thrust of this paper was to understand the magnitude and direction of transparency, fairness, accountability, and reliability on corporate government issues of Nepalese insurance companies. Accomplished the quantitative paradigm of study as a blend of guided literature reviews. The study has been carried out based on the primary data with a structured questionnaire. All the stakeholders of insurance companies of Nepal are a population of the study and seventy-two respondents from different sectors are taken as a sample with stratified sampling method. Measurement of corporate governance issues measured on a five-point Likert scale method. The primary data is examined by descriptive as well as inferential statistics methods. Findings show that there is a significant impact of transparency, fairness, accountability, and reliability on the corporate governance issues of Nepalese insurance companies. However, transparency of the activities is a major key element in maintaining corporate governance issues.